Electrically small antenna with circularly polarized and omnidirectional radiation pattern - Lertsakwimarn, Kittima; Phongcharoenpanich, Chuwong; Fukusako, Takeshi (My University, 2014)
This paper deals with the design of a circularly polarized electrically small antenna that has an omnidirectional radiation pattern. The antenna which consists of a horizontal loop element enclosed with two U-shaped elements and a vertical element. The proposed antenna has a dimension of 48 mm × 20 mm × 13.8 mm (0.14λ × 0.06λ × 0.04λ) with ka = 0.476 (i.e. <0.5), where k is the wavenumber at the resonant frequency and a is the radius of a sphere surrounding the antenna. The measured results of the omnidirectional circular polarization (CP) pattern and the simulated results are in good agreement.